Фізичне виховання в закладах вищої освіти в рамках європейської інтеграції - Іващенко, Олена; Ivashchenko, Olena (Видавництво МДПУ ім. Б. Хмельницького, 2023)
Сьогодні глобалізація глибоко проникла в освітню сферу, сприяючи інтеграції національних освітніх систем. Розвиток вищої освіти України на початку ХХІ століття орієнтоване на реалізацію положень Болонської декларації, яка сприятиме входженню України до країн Європейського співтовариства. Цей процес спрямований на розширення доступу до європейської освіти і, отже, підвищення його конкурентоспроможності. Все це відбувається в рамках Болонської декларації Today, globalization has deeply penetrated the educational sphere, contributing to the integration of national educational systems. The development of higher education in Ukraine at the beginning of the 21st century is focused on the implementation of the provisions of the Bologna Declaration, which will contribute to Ukraine's entry into the European Community. This process is aimed at expanding access to European education and, therefore, increasing its competitiveness. All this happens within the framework of the Bologna Declaration
Physical education in institutions of higher education within the framework of European integration
Keywords: фізичне виховання; physical education; освітня політика; educational policy; європейський освітній простір; European educational space